Perception of Iconic Russian Elements by English Speakers: Experimental Data - M. V. Veselova (Дискурс, 2024)
Introduction. In recent years, the anthropocentric scientific paradigm has been actively developing and the experimental method of research in linguistics is becoming increasingly popular and relevant. This article is devoted to the experiment of studying the process of perception iconic lexis of the unfamiliar language. Scientific novelty of this study is determined both by the selected material and methods of presenting this material for consideration.Methodology and sources. The basis for the experiment was a survey for native English speakers who did not know the language of the target stimuli (Russian). To conduct the experiment, a corpus of verbs of motion was used (546 verbs, 2273 word usages). The corpus was selected from 12 novels of English literature of the 20-21st centuries, as well as contextual translations of these verbs into Russian. During the study, a group of respondents (106 people) of both genders, various social and age groups were offered 20 English contextual uses of phonetically motivated verbs of motion, which were pre-selected from the above-mentioned corpus of verbs. In each sentence, a verb of motion was highlighted, and also a sound recording of two Russian verbs was presented, which was a translation of the highlighted English verb and its synonym. The total number of responses was 2120.Results and discussion. Participants of the experiment were asked to choose one of two Russian words that corresponded to the highlighted English word in the best way. Respondents chose with great confidence 4 iconic verbs of motion out of 15 pairs of synonyms in which only one verb is phonetically motivated. In 3 cases, respondents more often preferred the non-iconic word. The remaining pairs of synonyms were divided approximately equally. The more developed syntax of the Russian language compared to English, which sometimes obscured the sound motivated basis of the word could be a possible reason for this. Conclusion. The results of the experiment show that the perception of phonetically motivated units of an unfamiliar language depends on many factors. Thus, native English speakers who do not speak Russian or who speak it at a minimal level do not perceive Russian iconic vocabulary in all cases. Simultaneously, statistically significant differences in the perception by people of different age groups and gender were not revealed during the experiment.